Evidence of Direct Toxicological Effects of Scorpion Venom on Central Nervous System in Tunisian Children - Mabrouk Bahloul; Basma Souissi; Olfa Turki; Mariem Dlela; Khaireddine Ben Mahfoudh; Mounir Bouaziz (Case Reports in Critical Care)
Background. Severe scorpion envenomation can lead to severe neurological manifestations, which are an indicator of the severity of the scorpion sting. The direct action of scorpion venom on the central nervous system can explain partly these neurological disorders. Methods and Findings. We report a case of severe scorpion envenomation in 16-month-old boy with no pathological history admitted in ICU for severe scorpion envenomation. The result of cerebral MRI agrees with the hypothesis of direct action of scorpion venom on the central nervous system. Patient had improved; however, he has kept as neurological sequelae language disorders and blindness. The boy was discharged 21 days after ICU admission. Conclusion. Our observation confirms that severe scorpion envenomation can be complicated by severe neurological manifestations. Although one case report is not enough to conclude such important hypothesis regarding the direct effect of scorpion venom on central nervous system (especially that the age of patient is more than one year), our case agrees with this hypothesis.